Public Management and Organizational Reform in a Historical Perspective: The Case of Chile’S State Reform and Public Management Modernization of 1920s - Olavarria-Gambi, M (Routledge, 2018)
Applying the documental historical and hermeneutical methods as well as the policy process perspective, this article analyzes why and how the government machinery change. The analysis focuses on the modernization of public management and State reform, which occurred in Chile in the 1920s. It concludes that when dealing with changes in government organization and/or structure, management and organizational studies converge with analysis of policy change, particularly with the policy formulation process. Information on the issue comes from presidential addresses, bills sent to Congress, parliamentary discussions, press clippings, publications of interest groups and academic literature. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.